Movement ecology of captive-bred axolotls in restored and artificial wetlands: Conservation insights for amphibian reintroductions and translocations - Alejandra G. Ramos; Horacio Mena; David Schneider; Luis Zambrano (PLoS ONE, 2025)
Amphibians are among the most endangered vertebrates globally due to habitat loss, environmental degradation, and urban expansion. The axolotl ( Ambystoma mexicanum ), a critically endangered aquatic species endemic to Lake Xochimilco, exemplifies these challenges. This study evaluates the viability of restored and artificial wetlands for axolotl conservation by comparing movement patterns, home range sizes, and habitat use. Using VHF telemetry, we tracked captive-bred axolotls released into both environments. Axolotls survived and foraged successfully in both sites, with those in an artificial pond in La Cantera Oriente exhibiting larger home ranges (mean: 2,747 m²) and greater daily distances traveled than those in a restored chinampa in Lake Xochimilco, where home ranges were smaller (mean: 382 m²). A quadratic relationship between water temperature and movement indicated a narrow thermal preference, with axolotl movement peaking at around 16–17°C in Xochimilco and 15.5–16.5°C in La Cantera Oriente, declining beyond these ranges. Additionally, in La Cantera Oriente, female axolotls traveled significantly greater daily distances than males, with females averaging 86.75 meters per day compared to 54.33 meters for males. In Xochimilco, daily distance traveled decreased with age. Recaptured individuals gained weight, suggesting successful adaptation, although two axolotls were lost to avian predation in Xochimilco after the study concluded. These findings highlight the potential of artificial wetlands like La Cantera Oriente for axolotl conservation by providing stable conditions that may mitigate habitat degradation and climate change impacts. The study recommends integrating native and artificial habitats into conservation strategies, incorporating predator awareness training before release, and ongoing habitat monitoring to enhance survival outcomes for this iconic species.